Proyecto de factibilidad para la creación de una empresa dedicada a la industrialización, procesamiento y exportación de la madera de balsa como bloques encolados, al mercado de los Estados Unidos de América, ubicada en el cantón de Santo Domingo de los Tsáchilas - Molina Sánchez, Johana Elizabeth (2014)
Through this project a thorough analysis of the balsa wood industry in Ecuador is performed to obtain all the information needed to demonstrate the feasibility of creating a company that manufactures glued blocks and exported to the United States, for its market investigation reveals that Ecuador is known as the leading producer and exporter of balsa wood in the world, the U.S. being the largest consumer worldwide was performed. It has also established technology and more optimal production processes for manufacturing the bonded balsa blocks. The financial study allowed us to determine the major indices such as the net present value of $101,505.90 and the internal rate of return of 21.43%, so the viability of this project with the proposed funding was found.